PROSES PENYELESAIAN PELANGGARAN TERHADAP HAK ULAYAT MASYARAKAT ADAT BOTI KECAMATAN KI’E KABUPATEN TIMOR TENGAH SELATAN - Benu, Charles Boti; Hedewata, Agustinus; Usman, Siti Ramlah (Petitum Law Journal, 2024)
This research aims to find out how the process of resolving fiolates of the costumay rights of the Boti indigenous community, Ki’e district south central Timor regency and also the inhibiting facktot in the resolution process, this research is also expected to be able to contribute idea’s in efforts to understand insights in the field of civil law an in general, for the student community, this research writing is also considered as information for the general public regarding the problem under study, namely costomary rights. the Research method used in this research is empirical research or field studies,which is carried out directly at the actual research location using primary, secondary and tertiary data collection techniques through direct interviews at the research location with compotent respondents according to the problem being taken writer. The results of this research indiccate that the process of resolving violations of the customary rights of the Boti indigenous people is generally resolved by mediation of traditional consensus deliberation based on the principle because all Boti indigenous people have the same genes or blood ties so that traditional mediation is more appropriate to use in the process of resolving violations towards the customary rights of the Boti indigenous community.